1967
DOI: 10.1139/f67-043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oxygen Concentration on the Growth of Juvenile Largemouth Bass

Abstract: Experiments are reported on the influence of nearly constant dissolved oxygen concentrations, both below and above the air-saturation level, and of wide diurnal fluctuations of oxygen concentration on the appetite, growth, and food conversion efficiency of juvenile largemouth bass, Micropterus salmoides (Lacépède). The experimental apparatus used was designed to provide constant flows of water at 26 C and with controlled oxygen content through 12-gal (45-liter) bottles each containing 10 test fish. The fish we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
3

Year Published

1980
1980
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 1 publication
3
50
0
3
Order By: Relevance
“…Our laboratory experiments showed that growth was initially reduced at 50% O 2-saturation in dab and 30% O 2-saturation in plaice Even if some adaptation to low oxygen (30% O 2-saturation) occurred during the second part of the experiment, a significant overall reduction in growth was found for both species during a 20 d period Converting length into weight using the relationships described in Pihl (1989b) indicates that the normoxic growth rates for plaice and dab in our experiments are in general agreement with those (1 5-3 0% weight d -1 ) measured in the SE Kattegat Studies on other fish species, especially freshwater species, have shown° (Herrmann et al 1962, Stewart et al 1967, Adelman & Smith 1970, Andrews et al 1973, Brett & Blackburn 1981, Pedersen 1987 Our field data suggests that parts of the plaice and dab stocks could be exposed to hypoxia during at least 20 days periods, and for up to 3 months each year to moderate hypoxia Comparable exposures in the laboratory study resulted in reduced growth It is likely that repeated and increasing physiological stress from hypoxia during autumn would result in a long-term decrease in population mean length However other factors may also affect the length distribution of dab and plaice during the study period The most possible factors are variation in recruitment and availability of food resources Recruitment of plaice and dab have been investigated in shallow water in the adjacent Laholm Bay during the period 1980 to 1986 During this period no significant trend in recruitment strength, settling time or mean size of 0-or 1 groups were found for the two species (Pihl 1989b) In addition, the number of small-size recruiting individuals was insignificant in our study due to size-selection of the gear, and age-and size-dependent depth distribution of both species Juveniles of plaice and dab spend their first 2 years at water depths less than 10 m and join the parental stock during start of maturity the third year (Pihl 1989b) Thus, the observed reduction in mean length of the adult plaice and dab stocks may not be due to specific patterns in recruitment of juveniles Benthic infauna is the main food for plaice and dab in the SE Kattegat (Bagge et al ', Degel & Gislason,5 Pihl 1994) The total biomass of benthic infauna has shown a significant increasing trend over the last decades in areas without severe hypoxic events (Pearson et al 1985, Josefson 1990 …”
Section: Discussionsupporting
confidence: 82%
“…Our laboratory experiments showed that growth was initially reduced at 50% O 2-saturation in dab and 30% O 2-saturation in plaice Even if some adaptation to low oxygen (30% O 2-saturation) occurred during the second part of the experiment, a significant overall reduction in growth was found for both species during a 20 d period Converting length into weight using the relationships described in Pihl (1989b) indicates that the normoxic growth rates for plaice and dab in our experiments are in general agreement with those (1 5-3 0% weight d -1 ) measured in the SE Kattegat Studies on other fish species, especially freshwater species, have shown° (Herrmann et al 1962, Stewart et al 1967, Adelman & Smith 1970, Andrews et al 1973, Brett & Blackburn 1981, Pedersen 1987 Our field data suggests that parts of the plaice and dab stocks could be exposed to hypoxia during at least 20 days periods, and for up to 3 months each year to moderate hypoxia Comparable exposures in the laboratory study resulted in reduced growth It is likely that repeated and increasing physiological stress from hypoxia during autumn would result in a long-term decrease in population mean length However other factors may also affect the length distribution of dab and plaice during the study period The most possible factors are variation in recruitment and availability of food resources Recruitment of plaice and dab have been investigated in shallow water in the adjacent Laholm Bay during the period 1980 to 1986 During this period no significant trend in recruitment strength, settling time or mean size of 0-or 1 groups were found for the two species (Pihl 1989b) In addition, the number of small-size recruiting individuals was insignificant in our study due to size-selection of the gear, and age-and size-dependent depth distribution of both species Juveniles of plaice and dab spend their first 2 years at water depths less than 10 m and join the parental stock during start of maturity the third year (Pihl 1989b) Thus, the observed reduction in mean length of the adult plaice and dab stocks may not be due to specific patterns in recruitment of juveniles Benthic infauna is the main food for plaice and dab in the SE Kattegat (Bagge et al ', Degel & Gislason,5 Pihl 1994) The total biomass of benthic infauna has shown a significant increasing trend over the last decades in areas without severe hypoxic events (Pearson et al 1985, Josefson 1990 …”
Section: Discussionsupporting
confidence: 82%
“…Similar effects of low oxygen concentration on growth rates have been recorded by several authors for a number of fish species (e.g. Adelman and Smith 1970, Fisher 1963, Swift 1963, Stewart et al 1967). …”
Section: Low-oxygen Water and Rock Lobsterssupporting
confidence: 85%
“…Too few experimental studies on how fish respond to such conditions have been done to develop a consensus on a standard response. Stewart et al (1967) and Whitworth (1968) both found that fish exposed to intermittently low and high DO had lower growth rates than fish exposed to the mean DO concentration. A review of the subject by Brett (1979) concludes that exposure to sub-critical DO levels for only a portion of the day is enough to depress the growth rate to that comparable with the constant low DO concentration.…”
Section: Discussionmentioning
confidence: 97%